Pulmonary sarcomatoid carcinoma presenting both ALK rearrangement and PD-L1 high positivity: A case report on the therapeutic regimen. Issue 32 (August 2019) - D'Antonio, Federica; De Sanctis, Rita; Bolengo, Isabella; Destro, Annarita; Rahal, Daoud; De Vincenzo, Fabio; Santoro, Armando
Abstract: Rationale: Pulmonary sarcomatoid carcinoma (PSC) represents <1% of all lung cancers and is characterized by a very poor prognosis. The optimal therapeutic regimen remains unclear. We describe a rare case of PSC with both anaplastic lymphoma kinase (ALK)-arranged and high levels of programmed death ligand 1 (PD-L1) expression. Patient concerns: A 46-year-old woman, nonsmoker, came to our attention due to uncontrolled pain in the lower left limb. Diagnosis: PSC with both ALK rearrangement and high levels of PD-L1 expression. Interventions: The patient started first-line systemic treatment with pembrolizumab reporting stable disease; at progression, she received second-line treatment with crizotinib. The treatment was not well-tolerated, and the patient then underwent 5 cycles of ceritinib treatment. Outcomes: The patient showed a partial response to targeted therapy. At progression, brigatinib was initiated, but the patients reported liver progression soon after the initiation of this therapy. Lessons: Molecular-driven investigation is necessary in PSC for treatment selection.